CONSUMPTION TRENDS AND GENERATION CROSS INVESTMENT PATTERNS - Budiana, Hendy Purwanto (Penerbit Atma Jaya Catholic University of Indonesia, 2019)
William Strauss and Neil Howe (1991) classify that there are five (5) generations in the world. This distribution is done based on the time zone of each generation was born. The events and situations that existed at each time this generation was born to have shaped their characteristics in such a way that they are different from each other. In relation to humans as economic agents, all of these generations are not spared from economic activities, one of which is consumption. In this paper, the author intends to present information about how consumption patterns differ for each generation and how they relate to their investment patterns.